Comparison of herpetofaunal species diversity between adjacent limestone and sandstone habitats at Gunung Penrissen, Padawan, Sarawak (Borneo) - Nurnadia Marshita, Binti Abdul Aziz (Universiti Malaysia Sarawak (UNIMAS), 2012)
A study on comparison of herpetofaunal species diversity between adjacent limestone and sandstone habitat at Gunung Penrissen, Padawan, Sarawak (Borneo) was conducted. Sampling took place over a period of 12 days-17 January, 2012 to 23 January, 2012 for limestone habitat and on 9 February, 2012 to 14 February, 2012 for sandstone habitat. Besides two hours time constrained method, there were eight pitfalls traps and six glue traps were set at each sites. A total of 109 individuals, representing nine families comprising 18 genus and 21 species were recorded. Of these, 58 individuals were from limestone habitat comprising six families and 10 species. The most abundant species on that limestone habitat was Philautus tectus with 18 individuals were recorded. A total of 51 individuals were from sandstone habitat, comprising nine genus and 16 species. The most abundant species at the sandstone habitat was Leptobrachella mjobergi, with 16 individuals. Using pitfall trapping, two species were recorded Hylarana picturata and Cyrtodactylus consobrinus and two species recorded using glue traps, Eutropis rudis and Cyrtodactylus consobrinus. Individuals caught using traps were recorded only on the limestone habitat. Analysis used in this study are DIVERS, Zar t-test, EstimateS, and chi-square test and results from the analysis showed that the sandstone habitat is more diverse than limestone habitat.